Soroprevalência da brucelose em equídeos de serviço em Minas Gerais, 2003-2004 - Danilo Guedes Junqueira Junior (2012)
This study aimed to assess the prevalence of brucellosis in equidae in Minas Gerais State through the official serological tests for cattle. Because there is no cutoff point established for the equidae in the present study evaluated the results for the following: 2-mercaptoethanol title 25 (2-ME (25)), 2-mercaptoethanol title 50 (2-ME (50)), serum agglutination test title 100 (SAT (100)). We found a prevalence of 2.39% per animal (2-ME(25)), 0.83% (2-ME (50)) and 1.38% (SAT (100)); focus on prevalence was 7 , 43% (2-ME(25)), 3.13% (2-ME (50)) and 3.76% (SAT (100)). In evaluating stratified, the stratum Vale do Rio Doce in all analysis presented greater prevalence and number of municipalities with positive animals. We also evaluated whether the factors sex, age and species had an association with positive results and the calculation of odds ratio proved to be no association. Thus, we conclude that the title 50 in the test of 2-ME may be of greater value for epidemiological studies because it reduces the number of false positives and were shown not to be a risk factor for the trait analyzed.